PENGARUH STATUS GIZI DAN PEMBELAJARAN SAINS TERHADAP PERKEMBANGAN FISIK MOTORIK ANAK DI TK AL ABRAR MAKASSAR - Nurdin (UNZAH Genggong, 2023)
This study aims to analyze the effect of nutritional status and science learning on children's physical and motor development at TK Al Abrar Makassar. The research method used is quantitative with an associative type of research that aims to determine the effect of two or more variables. The variables used in this study were nutritional status (X1), science learning (X2), and children's physical motor development (Y). The type of data used is primary data obtained from a questionnaire. The population and sample in this study were 50 students at TK Al Abrar with a purposive sampling method for determining the sample. In this study the data were analyzed using multiple linear regression tests. The results of his research show that children in TK Al Abrar Makassar. This means that the higher the nutritional status, the higher the physical motoric development of children. There is a significant positive influence on science learning on children's physical motor development at TK Al Abrar Makassar. This means that the higher the science learning, the higher the child's motor development. There is an influence of nutritional status and science learning on the physical and motoric development of children in TK Al Abrar Makassar. Keywords: nutritional status, science learning, physical-motor development